La permanence d’une politique publique TIC - Philippe Vidal (Netcom)
The contents of a « digital city » project in Parthenay is studied on a ten-year period. This is probably one of the most emblematic French experiences regarding the introduction of ICT into urban environments. The project is one of the oldest in Europe. This article deals with the question of permanence of a public policy on ICT. It took ten years for the ICT sector to be organized within French spatial collectivities with an important rhythm. Three directions are developed in the article. First, showing the continuity of the Parthenay policy on ICT. Second, attempting to understand why the system has kept working even if there were decisive modulations modifying the initial spirit. Finally, trying to report the consequences of this project to local, national and European public actions in the creation of an information society model.